Electrochemistry of redox mediators encapsulated within organically modified silicate matrix in the presence of TiO2 and palladium nanoparticles; Application on electroanalysis of ascorbic acid - Pandey P.C.; Prakash A. (My University, 2025)
The encapsulation of redox mediators (i.e. ferrocene methanol, potassium ferricyanide) within the nanostructured network of organically modified silicate (ormosil) on a electrode surface is studied. The redox electrochemistry of modified electrodes made by sol-gel processing of 3-aminopropyltrimethoxysialne (3-APTMS) and 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane containing aqueous solution of desired redox mediators (potassium ferricyanide or ferrocene methanol) on electrode surface is reported. The synthetic protocol of ormosil film preparation on electrode surface also enables the encapsulation of titania (TiO2) and palladium when suitable precursors of the same are incorporated during sol-gel processing. The ormosil films are characterized by Atomic force spectroscopy, EDX and cyclic voltammetry. The modified electrodes of three different types (Ormosil, Ormosil-TiO2, and Ormosil-TiO 2-Pd) together with either ferrocene methanol or potassium ferricyanide are made to understand the redox behaviour of these electron transfer mediators present within nanostructured domain useful in electrochemical sensing with following major findings: (1) the redox electrochemistry of ormosil-encapsulated ferrocene methanol/potassium ferricyanide show gradual improvement in reversible electrochemical behavior in the order of Ormosil-TiO2-Pd > Ormosil-TiO2 and Ormosil; (2) the presence of TiO2-Pd in ormosil shows better catalytic activity as compared to that of made with only TiO2 toward ascorbic acid (AA) oxidation; (3) ferrocene methanol encapsulated ormosil has been found relatively more efficient mediator as compared to that of potassium ferricyanide toward AA oxidation. The findings justify the novel approach on the fabrication of porous chemically modified electrode of suitable nanogeometry for electroanalytical applications. © 2014 Elsevier B.V. All rights reserved.